Phytochemical test of 3 wild rambutan (Nephellium Lappaceum L. - Sapindaceae) fruits from Riau Province - Fitmawati; Sofiyanti, Nery; Isda, Mayta Novaliza; Agesti, Asih Rahayu Ajeng; Sari, Maya; Pranata, Syafroni (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Rambutan (Nepelium lappaceum) is one of tropical fruit plant that poses high morphological character, both cultivated or wild plants. The exploration of Nephellium in Riau Province had indicated 3 variations of wild Nephellium (Mone, Tunyiang dan Rambutan Hutan). The aim of this study was to examined the phytochemical contents of fruit from three wild Nephellium from Riau Province. Samples used in this study were three fruit parts (pericarp, aril and seed). Phytocemical tests were conducted qualitatively for alkaloid, terpenoid, steroid, flavonoid, saponin and tannin. The result showed that each fruit part had different phytochemical contents. Alkaloid was only found in aril of all wild Nephellium (Mone, Tunyiang dan Rambutan Hutan). Terpenoid and saponin were found in all fruit parts, while saponin was absent in all fruit parts from three wild Nephellium. ditemukan pada semua bagian buah dari ketiga buah rambutan liar. The result of this study provides additional information of phytochemical content of wild N. lappaceum.